2009
DOI: 10.1002/dmrr.969
|View full text |Cite
|
Sign up to set email alerts
|

Pulse pressure and cardiovascular autonomic neuropathy according to duration of type 1 diabetes

Abstract: Background To evaluate changes in pulse pressure (PP) and markers of cardiovascular autonomic neuropathy (CAN) according to duration of type 1 diabetes mellitus (T1DM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 52 publications
(104 reference statements)
5
42
0
Order By: Relevance
“…The squatting test may be used as an alternative dynamic procedure to assess the baroreflex gain [8,38,39]. During the transition from squatting to standing, there is an abrupt drop in BP associated with a reflex tachycardia, and these initial changes are followed by a rapid return to baseline values of both parameters (secondary BP increase and HR decrease) (Fig.…”
Section: Calculation Of the Baroreflex Gainmentioning
confidence: 99%
See 3 more Smart Citations
“…The squatting test may be used as an alternative dynamic procedure to assess the baroreflex gain [8,38,39]. During the transition from squatting to standing, there is an abrupt drop in BP associated with a reflex tachycardia, and these initial changes are followed by a rapid return to baseline values of both parameters (secondary BP increase and HR decrease) (Fig.…”
Section: Calculation Of the Baroreflex Gainmentioning
confidence: 99%
“…However, baroreflex gain was slightly but significantly decreased in overweight/obese subjects versus lean subjects and markedly decreased in elderly versus young individuals, also in agreement with data obtained from the pharmacological test using sequential nitroprusside-phenylephrine infusions [29] (Table 1). Finally, the changes in baroreflex gain measured during such a squatting test have been used to assess cardiac autonomic neuropathy in diabetic patients [8,38]. As an example, we previously reported that the baroreflex gain progressively decreased according to the duration of the disease in a population of patients with type 1 diabetes, whereas such reduction was not significant in a control nondiabetic population matched for age [8].…”
Section: Is a Clear Outlier In Our Seriesmentioning
confidence: 99%
See 2 more Smart Citations
“…Careful analysis of BP and HR changes during both transition states, from standing to squatting and from squatting to standing, respectively, provides interesting information as far as performance of baroreflexes and haemodynamic homeostasis are concerned (Rossberg & Penaz, 1988). For instance, the analysis of HR and BP changes occurring during a squatting test has been used by our group to assess orthostatic hypotension (Scheen et al, 1990), cardiovascular autonomic neuropathy (CAN) (Philips et al, 2009) and pulsatile stress (Philips et al, 2008); Philips et al, 2010a; Philips et al, 2010b) in patients with type 1 diabetes mellitus. Furthermore, squatting position is a long recognized therapeutic manoeuvre that can improve haemodynamics in patients with some congenital cardiac diseases (tetralogy of Fallot) (Lurie, 1953;Guntheroth et al, 1968).…”
Section: Non-invasive Continuous Monitoring Of Systolic and Diastolicmentioning
confidence: 99%